Low heating effects on the total microbial activity and physico-chemical properties of stingless bee (Heterotrigona itama) honey - Lee, Chuen Ng; Shamsul Bahri Abd Razak,; Rudiyanto,; Say, Peng Tan; Fauziah Tufail Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The high moisture content of stingless bee honey (SBH) is a worrisome problem and heat treatment is used to reduce the moisture and maintain the honey’s quality by destroying the microorganisms that affect the physico-chemical properties of honey during storage. Low heat treatment (45 °C) for 0, 30, 60, 90, and 120 min were conducted to determine the total microbial activity using fluorescein diacetate hydrolysis (FDA). The total microbial population that subsequently affected the physico-chemical properties was also analyzed. The total microbial activities of SBH were significantly reduced after thermal treatment at 45 °C for 90 min (63.76 μg FDA/g/h) and 120 min (62.43 μg FDA/g/h) compared with control (67.127 μg FDA/g/h). Also, the moisture content, electrical conductivity (EC), pH, and free acidity of the low heat-treated SBH at all durations were significantly reduced compared with the control. The total microbial activity was detected as significantly correlated to bacterial and fungal populations, moisture content, EC, pH, and free acidity of low heat-treated SBH. Low heat treatment at 45 °C for 120 min was efficient to reduce the total microbial activity, total acidity, and increasing the pH of SBH. Prolonging the heating duration is suggested to further reduce the water content, total microbial activity and further increase the shelf life of SBH.